Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species - Pereira, Antonio Marques Júnior; Marialva, Eric Fabrício; Julião, Genimar Rebouças; Pessoa, Felipe Arley Costa; Medeiros, Jansen Fernandes (Zootaxa, 2019)
Rondônia State has been subject to a higher percentage of deforestation than any other Brazilian state in the Amazon basin. Rondônia’s protected forests are extremely important because their biodiversity attests to the species richness that has been lost to human encroachment. Phlebotomine sand flies are Leishmania vectors that have the potential to function as environmental bioindicators. A sand fly survey was conducted near the Brazil-Bolivian border, in a protected ombrophylous forest in Guajará-Mirim State Park, which is located between the municipalities of Guajará-Mirim and Nova Mamoré, in Rondônia State, Brazil. A total of 6,341 specimens were collected and 59 species were identified; the most abundant species were Trichophoromyia auraensis (Mangabeira), Nyssomyia antunesi (Coutinho) and Trichophoromyia ubiquitalis (Mangabeira). Additionally, a new sand fly species of the genus Pintomyia (Lima) was discovered and is described herein. This new species belongs to the Pifanomyia Ortiz & Scorza subgenus, Serrana group, and is characterized by parameres with a basal area that is clearly more dilated than the apical area. The high diversity and abundance of sand fly vectors observed in this study, such as Ny. antunesi, Th. auraensis and Th. ubiquitalis, indicate that these species are probable vectors within Rondônia State. In addition, the discovery of a new Pintomyia species increases the number of sand fly species in Rondônia to 136, which demonstrates that high sand fly diversity within the region holds great potential for yielding important new discoveries.